Expanding the Vote Base in Uttar Pradesh: Understanding the RSS-BJP Combined Mobilization Strategies - Avishek Jha (South Asia Multidisciplinary Academic Journal, 2021)
The Sangh Parivar has essentially merged the registers of Mandal and Mandir by way of creating a viable political block for themselves in Uttar Pradesh. Based on an ethnographic study of the Sangh Parivar in Rampur, Uttar Pradesh and through interviews and participant observation, the article examines the roles played by various elements of the Sangh Parivar in expanding the vote base of the party. First of all, the article analyzes how the Sangh Parivar uses the strategies of social engineering and politicization of diverse identities to attract communities who traditionally have not voted for the party. Secondly, it examines the Sangh Parivar’s abilities to respond to local factors and develop political alliances within constituencies with varied demographics without compromising its core principles. Lastly, the article documents how the Rashtriya Swayamsevak Sangh functions like a corporation, with a committed workforce and clear division of responsibilities, and engages in electoral and political mobilization.